Emotion language in context: investigating emotion words in children’s written language and word learning - Dong, Y (2025)
The overarching aim of my thesis is to examine emotion language in children’s reading and writing, and the learning of new emotion words by adults and children. Understanding emotion words is crucial for emotional concept development, but few studies have considered emotion words beyond early childhood, or in the context of written language. This is an important gap as children experience language through reading emotional narratives, and this brings opportunities to learn new words and abstract concepts. Little is known about the potential influence that the emotional valence of the text might have on word learning. The thesis addresses these gaps in the literature through a combination of data-driven corpus analyses and experimental work.